Effect of pollination timing on the rate of apomictic reproduction revealed by RAPD Markers in Paspalum notatum - Espinoza, Francisco (2002)
Fil: Espinoza, Francisco. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Botánica del Nordeste; Argentina.